(untitled) (Memoria Americana. Cuadernos de Etnohistoria, 2000)
Reseña sobre el libro escrito por Ana María Alonso (1995) titulado Thread of blood. Colonialism, revolution and gender on Mexico’s northern frontier. Tucson, University of Arizona Press.